PKM Pelatihan Penyusunan Laporan Keuangan Berbasis Komputer Di Kelurahan Gendongan Kecamatan Tingkir Kota Salatiga - Tri Rinawati; Asih Niati; Yohanes Suhardjo (Jurnal ABM Mengabdi, 2021)
The problems faced by UKM in the Gendongan Village, Tingkir District, Salatiga City include the financial aspect that the financial management system applied is still manual, making it less effective and efficient. Manual bookkeeping there is no separation between personal finance and business finance. The solution offered is to provide training in preparing financial reports using Microsoft Excel. The approach method used in this activity is training. The training activities carried out included training in making simple bookkeeping in theory and training in making financial reports using Microsoft Excel applications. The solution to solving problems related to the problems faced by partners is to provide training and assistance by conveying material on computer-based financial reporting techniques using the Excel application.